2003
DOI: 10.1002/cyto.a.10016
|View full text |Cite
|
Sign up to set email alerts
|

Automated flow cytometry for acquisition of time‐dependent population data

Abstract: The system significantly expanded the utility of flow cytometry by eliminating cumbersome and time-consuming steps that make the application of flow cytometry impractical in certain situations. It is anticipated that the described set-up will find utility in biotechnology applications such as monitoring of cell cultures, screening of biologically active compounds, and in functional genomics efforts for phenotypic characterizations of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 15 publications
1
64
0
Order By: Relevance
“…However, if many techniques are available for the determination of cell physiology at a given moment of culture, dynamic evolution of microbial resistance to stress and adaptation is still poorly described. For this purpose, an automated version of FC has been proposed for the on-line monitoring of cell population heterogeneity under process-related conditions [73,74]. Specific interfaces comprising a mixing chamber where microbial cells are diluted prior to analysis and stained (if required) have been developed and commercialized.…”
Section: Flow Cytometry For On-line Bioprocess Monitoringmentioning
confidence: 99%
“…However, if many techniques are available for the determination of cell physiology at a given moment of culture, dynamic evolution of microbial resistance to stress and adaptation is still poorly described. For this purpose, an automated version of FC has been proposed for the on-line monitoring of cell population heterogeneity under process-related conditions [73,74]. Specific interfaces comprising a mixing chamber where microbial cells are diluted prior to analysis and stained (if required) have been developed and commercialized.…”
Section: Flow Cytometry For On-line Bioprocess Monitoringmentioning
confidence: 99%
“…Samples were automatically withdrawn from the bioreactor every 21 min and processed by the previously described automated cell preparation system (Abu-Absi et al 2003;Zhao et al 1999). A commercial version of such sample preparation system has been recently developed by MSP Corp, Shoreview, MN (http://www.mspcorp.com).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Therefore, it is of considerable interest to detect this heterogeneity, to monitor it online, and ultimately to control it with appropriate process conditions. To accomplish this, we developed an automated flow cytometry system (Abu-Absi et al 2003) that has already been shown to be useful for a variety of applications including monitoring of microbial (Kacmar et al 2004) and mammalian cell cultures (Kacmar and Srienc 2005). Automated flow cytometry can provide online cell number and viability, with the ability to discriminate subpopulations even if they are present as a small fraction of the total cell population.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier approaches to the CFSE data analysis were based upon assumption that there is no death in the proliferating lymphocytes. The histogram data were interpreted using a simple discrete doubling model [11,19] or the exponential growth model [1]. These models allowed to estimate the frequency of responding cells and the specific exponential growth rates, respectively.…”
Section: Introductionmentioning
confidence: 99%